Moral Education from Imam Nawawi's Perspective: An Analytical Study of the Kitab Nashaih Al-'Ibad - Wibawati Bermi; Darmanto Darmanto; Pratama Andika Putra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2024)
Moral education is a fundamental aspect of Islamic education, aimed at developing individuals with virtuous character and integrity. Imam Nawawi's Kitab Nashaih Al-'Ibad is a classical Islamic text that provides profound insights into moral education. Understanding these insights is crucial for enhancing contemporary Islamic education. This study aims to explore and analyze the concept of moral education from Imam Nawawi's perspective as presented in Kitab Nashaih Al-'Ibad. The research employs a library research methodology, with Kitab Nashaih Al-'Ibad as the primary reference and various other books and studies on Imam Nawawi's educational perspectives as secondary references. Data was collected through thematic analysis of the primary text and comparative analysis with existing literature on Islamic and moral education. Findings, The study identifies five key principles of moral education according to Imam Nawawi: sincerity (ikhlas), humility (tawadu), patience (sabar), gratitude (syukur), and self-accountability (muhasabah). These principles are highly relevant to contemporary Islamic education, offering a holistic approach that integrates moral and academic development. Comparisons with previous studies and theories highlight the universal relevance and applicability of these principles. Conclusion, Imam Nawawi's principles provide a robust framework for moral education that can significantly contribute to the development of virtuous individuals in the modern educational context. Effective implementation requires collaborative efforts among educators, communities, and stakeholders. Recommendations: It is recommended that these principles be integrated into the curriculum, teacher training programs, and community involvement initiatives. Further research is encouraged to explore practical applications and impacts of these principles in diverse educational settings.